TECHNICAL UNIVERSITY IN INFORMATIVE EPOCH: THE PROBLEM Of AUTONOMY (SOCIAL-PHILOSOPHICAL ANALYSIS) - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article is accented attention on the features of realization of idea of autonomy of universities in an informative epoch